A 2-Week Specific Volleyball Training Supported by the Whole Body Cryostimulation Protocol Induced an Increase of Growth Factors and Counteracted Deterioration of Physical Performance - Jaworska, Joanna; Micielska, Katarzyna; Kozłowska, Marta; Wnorowski, Krzysztof; Skrobecki, Jerzy; Radzimiński, Lukasz; Babińska, Anna; Rodziewicz, Ewa; Lombardi, Giovanni; Ziemann, Ewa (Frontiers in Physiology, 2018)
According to recent observations, on the one hand, applying cold treatment may support regeneration; on the other hand, it may attenuate training adaptation. We have, thus, decided to evaluate the effect a two-week volleyball training program supported by 10 sessions of whole body cryostimulation (WBC) on growth factors and physical performance. Twenty healthy college-aged men and women, randomly assigned either to the CRY (WBC treatment) or the CON (control, passive rest) group, took part in a two-week training program. The CRY group also attended cryo-sessions (3min, temperature, -110°C, 5 times/week) during this period. Blood samples were collected at baseline, 1h after the first and last session of WBC to assess growth factors, myokines and the amino acid profile. Motor abilities were tested at baseline and after the program’s completion. The applied intervention resulted in an increase of BDNF and IGF-1 concentrations. The adjusted effect was moderate and very likely in the CRY group, higher than in the CON one. Physical performance dropped in both groups, yet in the CRY group, the range of changes was smaller. The FGF21 concentration dropped significantly 1h following the first WBC session, yet irisin remained statistically unchanged. In the CRY group, an elevated uptake of tryptophan and valine, noted in response to the intervention, could have induced a significant decrease of fasting glucose concentration (effect small and very likely). Overall, a two-week volleyball training program supported by a WBC protocol resulted in an increase of growth factors and offset a decline of physical performance.